Lithium‐Ion Batteries: Experimental Studies on Work Functions of Li+ Ions and Electrons in the Battery Electrode Material LiCoO2: A Thermodynamic Cycle Combining Ionic and Electronic Structure (Adv. Energy Mater. 18/2018). Issue 18 (25th June 2018) - Schuld, Stephan; Hausbrand, René; Fingerle, Mathias; Jaegermann, Wolfram; Weitzel, Karl‐Michael
Abstract : In article number1703411, Karl‐Michael Weitzel and co‐workers describe a complete thermodynamic cycle for a LiCoO2 //Li battery. The approach takes into account not only electronic but also ionic contributions to the open circuit cell voltage. The experimental data originate from work function measurements, w(e − ) for electrons and w(Li + ) for ions from LiCoO2 .